Theoretical Investigation of Intermolecular Dihydrogen Bonds in C2H2···HM and C2H4···HM (M = Li, Na and K) Complexes: A DFT and ab initio Study - Parimala Devi, D.; Giju, Tom; Praveena, G.; Abiram, A. (Asian Journal of Chemistry, 2021)
This study aims to investigate the dihydrogen bond formation in ethyne (C2H2) and ethene (C2H4) with alkali metal hydrides (HM; M = Li, Na and K) complexes using density functional theory (DFT) and ab initio methods. It mainly focuses on the comparison of the performances of different functionals of DFT and ab initio method on the intermolecular dihydrogen bonded complexes. The geometrical parameter and energy values agree with the formation of dihydrogen bonds in the complexes. Among the ethyne and ethene complexes, the smallest dihydrogen bond distance was formed by C2H2···HK and C2H4···HK, respectively. The C2H2 is found to form better dihydrogen bond (DHB) with alkali metal hydrides than C2H4. Among all the functionals, M06L was observed to predict shortest H···H bond distance, while M062X the longest. Natural bond orbital (NBO), quantum theory of atom in molecules (QTAIM) along with molecular electrostatic potential (MEP) analysis further confirms the dihydrogen bond formation.